Analysis of Postmodern Elements in the Novel if on a winter's night a traveler Written by Italo Calvino - Hawar Sardar Ali (Zien Journals, 2023)
Today, we live in the postmodern era, whose traces and signs can be seen everywhere, and ironically, this new fashion of contemporary intellectualism is the most comprehensive cultural attack on non-Arab societies that has been experienced so far. In post-modern stories, we are not facing a plot, and it is as if some kind of destruction and collapse has occurred in the plot, so that no order and coherence can be seen in its plot Considering that postmodernism is one of the most important literary movements of the 20th century, and also because of the breadth and universality of this school, many researches have been conducted in this field, each of which has studied postmodernism from a specific perspective Based on what was mentioned, the purpose of the study is to Analyze of Postmodern elements in the Novel if on a winter's night a traveler written by Italo Calvino. The study is placed in the position of descriptive-analytical studies. A comparative and scrutinizing examination of different dimensions and angles of the novel if on a winter's night a traveler shows that there are obvious and similar postmodern components in it such as multiple endings, contradictions in characters, deconstruction, metafictional layer, para-narrative, and short circuit. The results of this research can greatly contribute to literary studies
Keywords: Postmodern Elements; Novel; if on a winter's night a traveler